Odpowiedzi

2010-02-27T13:41:33+01:00
A) 3(2x+3) 6x + 9
b)-2(7-2y) -14 + 4y
c)(2a+b)*(-5) -10a - 5b
d)1/2(4a+1) 2a + 1/2
e) -2/3(6y-9) -4y + 6
f)-0,2(-b-1) 0,2b + 0,2
g) -(4x+3-1/2y) -4x - 3 + 1/2y
h) -5(-3a+b-0,7) 15a - 5b +3,5
i) -(-1/2t-z-6) 1/2t + z + 6


LICZĘ NA NAJLEPSZY ^|^
1 1 1
2010-02-27T13:42:46+01:00
A]
3(2x+3)=6x+9
b]
-2(7-2y)=-14+4y
c]
(2a+b)×(-5)=-10a-5b
d]
½(4a+1)=2a+½
e]
-⅔(6y-9)=-4y+6
f]
-0,2(-b-1)=0,2b+0,2
g]
-(4x+3--½y)=-4x-3+½y
h]
-5(-3a+b-0,7)=15a-5b+3,5
i]
-(-½t-z-6)=½t+z+6
2010-02-27T13:42:46+01:00
A) 3(2x+3) = 3x + 9
b)-2(7-2y) = -14 + 4y
c)(2a+b)*(-5) = -10a + (-5b)
d)1/2(4a+1) = 2a + 0,5
e) -2/3(6y-9) = -4y + 6
f)-0,2(-b-1) = 0,2b + 0,2
g) -(4x+3-1/2y) = -4x - 3 + 1/2y
h) -5(-3a+b-0,7) = 15a - 5b + 3,5
i) -(-1/2t-z-6) = 1/2t + z + 6

Pozdro mam nadzieje że pomogłem